Monitoring for Results: Lessons from CAADP Frameworks - Badiane, Ousmane (2020)
Ousmane Badiane POLICY SEMINAR Virtual Event - Information Needs for Food Crisis Risk Early Warning: The Role of the Food Security Portal Co-Organized by IFPRI and the Food Security Portal (FSP) NOV 24, 2020 - 09:30 AM TO 11:00 AM EST